Nível de transparência da remuneração executiva e comportamento da remuneração variável em períodos de estabilidade e crise econômica - Andreoli, Paulo Henrique (2018)
While studies on executive compensation models that align the interests of shareholders and managers are increasing in Brazil, good corporate governance practices suggest greater transparency in the disclosure of executive compensation to the stakeholders. This paper aimed primarily at analyzing the level of transparency in the disclosure of executive remuneration at different moments of the Brazilian economy, in a period of stability and economic crisis and additionally, based on the data collected, understand the proportion of variable remuneration in different periods, figuring to observe if the variable remuneration paid to managers would be lower in the period of greatest economic difficulty. For a better comparative analysis, we selected three relevant, distinct, regulated and unregulated segments, such as food, banking and electric energy. Based on the main economic indicators, we selected the years 2012 and 2015, where we consider 2012 a year of economic stability in Brazil and 2015, a year of crisis. The results indicated that even in 2015, some segments analyzed showed a good performance in their results compared to 2012. The eventual decline in levels of disclosure of executive compensation, which could be expected, proved to be quite stable for both years. Even with adverse results among the segments in 2015, it was possible to observe that short term variable compensation was no longer used as a remuneration by some companies in the second year analyzed. A certain migration from short-term variable compensation to share based compensation was observed, and a significant increase in the average values paid through this type of incentive in two of the three segments analyzed. The observed behavior illustrates several studies on the subject and the good practices of corporate governance in showing the search for the alignment of the interests of the shareholders and managers and balance of goals between short and long term, especially in times of greater economic difficulty.